Analisis Fenomena Budaya Ngopi Sebagai Gaya Hidup Generasi Millenial (Studi Kasus pada Coffee Shop Pasco Bagan Batu Riau) - Husna, Isnaini; Ramadhani, Sri; Ilhamy, Muhammad Lathief (CV. ITTC INDONESIA, 2023)
This study aims to find out how the cultural phenomenon coffee as a lifestyle for the millennial generation and how things form millennial generation lifestyle at Coffee Shop Pasco Bagan Batu Riau. Study This method uses a qualitative descriptive method. The type of data used in this study are primary and secondary data. Data collection technique through observation, interviews, and documentation. Informants in this study is Mr. Uqi Simasu as the owner of Coffee Shop Pasco. And visitors Coffee Shop Pasco. The data analysis technique in this study is data reduction, presentation of data, and drawing conclusions. The research results show the phenomenon of coffee culture as a lifestyle created through the Coffee Shop. Pasco is like hanging out with friends, chatting, discussing regarding work, doing college assignments and office assignments. As well as results research shows that there is an interest in the millennial generation for cafes. Pasco, so that the millennial generation really likes to visit the Coffee Shop Pasco. The phenomenon that occurs shows that the existence of Coffee Shop Pasco is one of the cultures as a lifestyle for the millennial generation at this time.Where Coffee Shop Pasco has become a place to facilitate generations millennials in carrying out one's activities, interests and opinions so that creating a coffee culture as a lifestyle for the millennial generation at this time.